Ecophilosophy of Semen Antonets, regarding organic farming as a method of non-traditional land use - Sharyi, H. (Land Management, Cadastre and Land Monitoring, 2024)
The paper analyzes the scientific works and elaborates the technological aspects and significance of the unique system of organic agriculture of the outstanding scientist-innovator, Hero of Ukraine Semen Antonets.It is emphasized that the Poltava agrarian and scientist Semen Antonets, back in the 70s of the last century, formed philosophical approaches in the field of nature management based on the principles of harmony with the natural environment, due to the implementation of the organic farming system as a method of non-traditional land use.The eco-philosophical orientation and special ecological ethics of the life path and heritage of the famous agrarian, scientist Semyon Antonets, which correspond to the teachings of V. Vernadskyi, the philosophy of H. Skovoroda, H. Skolimovski, and A. Ness, are determined.It has been proven that Semen Antonets proved the truth of the ecological conclusions he defined with fifty years of practical experience, the real implementation and existence of organic farming in the enterprise "Agroecology" of the Poltava region, which has not used chemical substances and mineral fertilizers since 1978.It is emphasized that the paradigm of organic agriculture of Semyon Antonets develops ecophilosophical teaching, contributing to an ecological worldview and universal ecological humanism and thinking.The need for legal protection of organic farming enterprises, and especially the lands of the Agroecology State Enterprise, and their preservation for future generations, has been elaborated.
Keywords: Semen Antonets; ecophilosophy; organic farming; soil; natural resources; environmental ethics; unconventional land use